(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. This article analyzes the importance of the English language in the field of medicine, its role in international scientific and practical communication, as well as its necessary aspects for medical workers. In the context of globalization, the role of the English language in the development of medical science and international exchange of experience is incomparable. The article highlights the importance of using English in scientific articles, textbooks, conferences and clinical practice.